Separation and determination of impurities in paracetamol, codeine and pitophenone in the presence of fenpiverinium in combined suppository dosage form - Vojta, Jiří; Hanzlík, Pavel; Jedlička, Aleš; Coufal, Pavel (Journal of pharmaceutical and biomedical analysis, 2015)
A new HPLC method for separation and determination of impurities in paracetamol, codeine phosphate hemihydrate and pitophenone hydrochloride in the presence of fenpiverinium bromide in combined suppository dosage form was developed and validated. The separation of paracetamol and its impurities 4-aminophenol, 4-nitrophenol, 4-chloracetanilid; codeine and its impurities methylcodeine, morphine, codeine dimer and 10-hydroxycodeine; pitophenone and its impurities 2-[4-[2-(1-piperidinyl)ethoxy]benzoyl] benzoic acid, 2-[4-[2-(1-piperidinyl)ethoxy]benzoyl]benzoic acid 2-(1-piperidinyl)-ethyl ester, methyl ester of 2-(4-hydroxybenzoyl) benzoic acid and fenpiverinium was achieved by using ion-pair reversed phase liquid chromatography with UV detection. Validation parameters such as the precision, accuracy, linearity, limit of detection (LOD), limit of quantification (LOQ) and robustness were verified for all the mentioned impurities of codeine phosphate hemihydrate and 4-aminophenol and 2-[4-[2-(1-piperidinyl)ethoxy]benzoyl] benzoic acid as the main degradation products of paracetamol and pitophenone hydrochloride, respectively. The described method was found to be useful for analysis of the stability samples and therefore suitable for routine purity testing of the drug product.
Keywords: Codeine; molekulární struktura; Benzophenones; Drug Contamination; Molecular Structure; kontaminace léku; čípky; Piperidines; Suppositories; paracetamol; piperidiny; Acetaminophen; Chromatography, Reverse-Phase; kodein; chromatografie s reverzní fází; benzofenony